1989
DOI: 10.1099/0022-1317-70-6-1493
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing Epitopes of Type O Foot-and-Mouth Disease Virus. II. Mapping Three Conformational Sites with Synthetic Peptide Reagents

Abstract: SUMMARYFour neutralizing monoclonal antibodies (MAbs), recognizing three functionally independent, conformational sites on type O foot-and-mouth disease virus (FMDV) failed to react with immobilized structural proteins or synthetic peptides but bound to the isolated capsid protein VP1 and peptides in solution. Inhibition ELISA techniques were, therefore, applied using peptide antigens and anti-peptide sera to block MAb binding to virus particles, permitting the identification of those portions of the VP1 prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
35
0
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(39 citation statements)
references
References 26 publications
3
35
0
1
Order By: Relevance
“…Comparison of the P1 amino acid sequences of the SAT2 viruses indicated that the variation observed was confined to hypervariable loops of which five were identified in VP1 and one each in VP3 and VP2. The structural orientation of these variable loops on the capsid correlates strongly with previously identified neutralizing epitopes of type A (Baxt et al, 1989;Thomas et al, 1988) and O Crowther et al, 1993a;Kitson et al, 1990;Parry et al, 1989) viruses. The hypervariable regions may act as topographical regions for binding of soluble scFv1 or scFv3 on the virus capsid and the variation observed in reactivity of these soluble scFvs to the panel of SAT2 virus might be a reflection of the amino acid variation in these regions.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Comparison of the P1 amino acid sequences of the SAT2 viruses indicated that the variation observed was confined to hypervariable loops of which five were identified in VP1 and one each in VP3 and VP2. The structural orientation of these variable loops on the capsid correlates strongly with previously identified neutralizing epitopes of type A (Baxt et al, 1989;Thomas et al, 1988) and O Crowther et al, 1993a;Kitson et al, 1990;Parry et al, 1989) viruses. The hypervariable regions may act as topographical regions for binding of soluble scFv1 or scFv3 on the virus capsid and the variation observed in reactivity of these soluble scFvs to the panel of SAT2 virus might be a reflection of the amino acid variation in these regions.…”
supporting
confidence: 64%
“…The likelihood that the residue change at position 159 of VP1 forms part of an antigenic site on the SAT2 capsid is supported by the fact that residue 159 of VP1 forms part of the base of the G-H loop and the G-H loop residues 140-160 have been shown to play an important role in antigenicity in most FMDV serotypes Bolwell et al, 1989;Crowther et al, 1993a;Parry et al, 1989;Pfaff et al, 1988;Thomas et al, 1988). The antigenic sites Ia and Ib of SAT1 viruses, for example, involve residues on both sides of the RGD motif in the G-H loop (Grazioli et al, 2006).…”
mentioning
confidence: 85%
“…This suggests that the corresponding linear epitope, which was characterized with synthetic peptides (Van der Heijden et al, 1993) also belongs to minor antigenic site c. Therefore the peptide strategy indicates as highly immunodominant a region of the G protein which is only recognized by half of our WB + MAbs, a category which represents only 2% of our MAbs. Should this observation be generalized, it would mean that the peptide approach, although it has been successfully used to map some neutralizing epitopes of viral antigens (Muller et al, 1982;Parry et al, 1989;Rini et al, 1993) is not suitable for the characterization of complex major antigenic sites as those of rabies virus G protein.…”
Section: Discussionmentioning
confidence: 99%
“…The antigenic site A of TGE virus may resemble one of the neutralization epitopes of foot-and-mouth-disease virus, shown recently to be formed by two separated antigenic regions (Thomas et al, 1988;Parry et al, 1989). Hu et al (1987) reported that a TGE virusneutralizing MAb recognized E2 protein fragments expressed in E. coli, representing residues 378 to 601; this region contains the residues 538 and 543 involved in site A formation.…”
Section: Discussionmentioning
confidence: 99%